2016
DOI: 10.1097/md.0000000000004653
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of computed tomography from organ-selective to whole-body scanning in managing unconscious patients with multiple trauma

Abstract: We aimed to evaluate the benefit of whole-body computed tomography (WBCT) scanning for unconscious adult patients suffering from high-energy multiple trauma compared with the conventional stepwise approach of organ-selective CT.Totally, 144 unconscious patients with high-energy multiple trauma from single level I trauma center in North Taiwan were enrolled from January 2009 to December 2013. All patients were managed by a well-trained trauma team and were suitable for CT examination. The enrolled patients are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… 7 Different studies reported similar results except for the study by Mao et al and their findings are presented in Table 1 . 7 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 …”
Section: Is the Traditional Sct Approach A Time-consuming Method?mentioning
confidence: 99%
“… 7 Different studies reported similar results except for the study by Mao et al and their findings are presented in Table 1 . 7 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 …”
Section: Is the Traditional Sct Approach A Time-consuming Method?mentioning
confidence: 99%
“…One SR [ 29 ] including three studies investigated hospital stay cost-based parameters. Two primary studies [ 37 , 38 ] conducted in Taiwan and Europe discovered that the costs associated were not statistically significant between routine WBCT and non-routine WBCT. Particularly, data reported from a multicentre RCT showed that the hospital costs of European hospital stay were €24 967 (95% CI 21 880–28 752) for the WBCT group and €26 995 (23 326–30 908) for the standard work-up group ( p = 0.44).…”
Section: Resultsmentioning
confidence: 99%
“…In hemodynamically stable patients with suspected ab-dominal trauma and decreased mentality, abdominal CT has been reported to diagnose hidden abdominal trauma and lower the mortality rate [63,64]. Negative results on abdominal CT show very high specificity for excluding abdominal damage, shortening the hospital stay for follow-up [65].…”
Section: Evidence Review or Evidence Summarymentioning
confidence: 99%